Organised Labour, Labour Market Imperfections, and Employer Wage Premia - Sabien Dobbelaere; Boris Hirsch; Steffen Müller; Georg Neuschäffer (Tinbergen Institute, 2020)
This paper examines how collective bargaining through unions and workplace co-determination through works councils shape labour market imperfections and how labour market imperfections matter for employer wage premia. Based on representative German plant data for the years 1999-2016, we document that labour market imperfections are the norm rather than the exception. Wage mark-downs, that is wages below the marginal revenue product of labour rooted in employers' monopsony power, are the most prevalent outcome. We further find that both types of organised labour are accompanied by a smaller prevalence and intensity of wage mark-downs whereas the opposite holds for wage mark-ups, that is wages above the marginal revenue product of labour rooted in workers' monopoly power. Finally, we document a close link between our production-based labour market imperfection measures and employer wage premia. The prevalence and intensity of wage mark-downs are associated with a smaller level and larger dispersion of premia whereas wage mark-ups are only accompanied by a higher premium level.
Keywords: D22; J42; J50; J31; 330; Wage mark-downs; wage mark-ups; collective wage agreements; works councils; employer wage premia